Bullying in the workplace : causes, symptoms, and remedies - Crothers, Laura M.; Lipinski, John. (New York : Routledge, 2014)
Bullying in the workplace is a phenomenon that has recently intrigued researchers studying management and organizational issues, leading to such questions as why it occurs and what causes such harassment. This volume written by experts in a wide range of fields including Industrial and Organizational psychology, Counseling, Management, Law, Education and Health presents research on relational and social aggression issues which can result in lost productivity, employee turnover and costly lawsuits. Understanding this phenomenon is important to managers and employee morale. -- Provided by publisher
Includes bibliographical references and indexes.
Keywords: Bullying in the workplace; Bullying in the workplace